Reciprocal control of catalysis by the tyrosine recombinases XerC and XerD: an enzymatic switch in site-specific recombination. - Hallet, B; Arciszewska, L; Sherratt, D (1999)
In Xer site-specific recombination, sequential DNA strand exchange reactions are catalyzed by a heterotetrameric complex composed of two recombinases, XerC and XerD. It is demonstrated that XerC and XerD catalytic activity is controlled by an interaction involving the C-terminal end of each protein (the donor region) and an internal region close to the active site (the acceptor region). Mutations in these regions reciprocally alter the relative activity of XerC and XerD, with their combination producing synergistic effects on catalysis. The data support a model in which C-terminal intersubunit interactions contribute to coupled protein-DNA conformational changes that lead to sequential activation and reciprocal inhibition of pairs of active sites in the recombinase tetramer during recombination.